The Role of Civil Society Organizations in Promoting Social Inclusion among Rural Dwellers in Nigeria : Array - Akinyetun, Tope Shola; Erubami, Hungevu Paul; Salau, Adewale Jamiu; Bakare, Tope Oke; Ahoton, Aihonsu Samuel (Acta Universitatis Danubius. Relationes Internationales, 2021)
What are civil society organizations? What are their functions? Are they relevant? How are they perceived? Do they promote social inclusion? Are they known by rural dwellers? These germane questions led to this study. The general objective of the study is to examine the perception of rural dwellers on the role of civil society organizations (CSOs) in promoting social inclusion in Nigeria, using rural areas of Lagos and Ogun states as a case study. The study adopts a survey research design and utilized a structured questionnaire as the research instrument. Eight hundred questionnaire was administered to rural dwellers selected from twenty towns; twenty districts; and forty streets of Badagry and Ipokia Local Government Areas (LGAs) of Lagos and Ogun states respectively, using a multistage and random sampling technique. Quantitative data were analyzed using descriptive statistics and chi-square inferential statistics. Findings show that although rural dwellers of Lagos and Ogun states know of the existence of CSOs, they are not properly informed of their functions. The result also yields evidence that rural dwellers are not convinced of the relevance of CSOs and their role in social inclusion. The study, therefore, recommends that CSOs should intensify their efforts of social inclusion in rural areas and engage more rural dwellers of Nigeria in their programmes, particularly in the rural areas of Lagos and Ogun states. This, the study argues, is necessary for engendering sustainable development.